Multi‐Unit Needleless Electrospinning for One‐Step Construction of 3D Waterproof MF‐PVA Nanofibrous Membranes as High‐Performance Air Filters. Issue 7 (11th December 2022) - Yan, Guilong; Yang, Zihao; Li, Jiayi; Li, Han; Wei, Jiabing; Shi, Letian; Li, Zhenyu; Chen, Jingyu; Wang, Li; Wu, Yuanpeng
Abstract: The airborne particulate matter (PM) seriously threatens people's health. Personal protective equipment with electrospun nanofibers is an effective method to make people away from air pollutants. Herein, 3D waterproof melamine‐formaldehyde polyvinyl alcohol (MF‐PVA) nanofibrous membranes are fabricated by a one‐step method combining multi‐unit needleless electrospinning and a thermal treatment device in a line. 3D nanofibrous structures can be controlled by adjusting the solution concentration of each unit. The PVA nanofibrous membranes become waterproof after cross‐linking with MF resin in the following thermal treatment device. The optimized MF‐PVA nanofibrous membrane shows excellent air filtration performance (97.3% for PM0.3, 100% for PM1.0, and 100% for PM2.5 ) and low air resistance (76 Pa). These 3D waterproof MF‐PVA nanofibrous membranes exhibit ultra‐stable performance in various practical environments. Abstract : 3D waterproof melamine‐formaldehyde polyvinyl alcohol (MF‐PVA) nanofibrous membranes for high performance air filtration can be constructed by a one‐step method combining multi‐unit needleless electrospinning and a thermal treatment device in a line.